An orthogonal simulated annealing algorithm for large floorplanning problems. - Shinn-Ying Ho (IEEE Transactions on VLSI systems)
The conventional simulated annealing with some random generation mechanism using the sequence-pair topological representation in block placement and floorplanning is effective for a very small number of modules (40-50). This paper proposes an orthogonal simulated annealing algorithm (OSA) with an efficient generation mechanism (EGM) for solving large floorplanning problems. EGM samples a small number of representative floorplans and then efficiently derives a high-performance floorplan by using a systematic reasoning method for the next move of OSA based on orthogonal experimental design. Furthermore, an improved swap operation is proposed which cooperates with EGM to make OSA efficient. Excellent experimental results using the Microelectronics Center of North Carolina and the Gigascale Systems Research Center benchmarks show that OSA performs better than existing methods for large floorplanning problems.